Caracterização estratigráfica, tectônica, metamórfica e geocronológica do Orógeno Araçuaí na região de São José da Safira Virgolândia, Minas Gerais - Eliza Inez Nunes Peixoto (2013)
The Araçuaí orogen, representing one of the various branches of the Neoproterozoic Brasiliano/PanAfrican orogenic system, developed between the São Francisco craton and its African counterpart, the Congo craton. This study conducted a structural, petrologic and geochronological detailed investigation on a rock assemblage that occurs along a roughly NS-trending belt located immediately to the west of the magmatic arc of the Araçuaí orogen in São José da Safira region (Minas Gerais state, southeastern Brazil). The ca. 30km-wide and 100 km-long belt of metasedimentary rocks focused in this study consists essentially of pelitic schists containing lenses and pods of quartzites, ultramafics, and deformed collisional granites. Thrust to the west on top of the Archean Guanhães basement block and separated on the east from the Ediacaran Rio Doce magmatic arc by a reverse-dextral fault zone, the belt exhibits the architecture of an asymmetric flower structure developed in a dextral transpressional regime. The distribution of metamorphic parageneses across the belt characterizes a Barrovian metamorphic zoning, in which the sillimanite, kyanite, staurolite and garnet zones are locally duplicated by thrusts. The metamorphic PT conditions range from ca. 700 °C and 7.5 kbar at the base of the schist pile on the west to ca. 550 °C and 5.5 kbar at the top of the package on the east. Zircon UPb geochronology indicates metamorphic overprinting on the top of the Archean basement (2.7-2.8 Ga) at 560 ± 20 Ma and emplacement of a collisional granite at 544 ± 10 Ma, implying that the collisional stage lasted up to the EdiacaranCambrian boundary. Maximum deposition ages around 819 Ma were obtained from zircons extracted from the lower portion of the schist package, which also shows age spectra and lithological assemblage similar to the passive margin strata involved in the orogen (Formação Ribeirão da Folha, Macaúbas Group). Zircons from the upper portion of the pile have yielded maximum deposition ages around 579 Ma, pointing toward the Rio Doce magmatic arc as their main source. Besides the maximum depositional age, the lithological similarities correlate this portion with Salinas Formation, a flysch-type orogenic basin. All together, these results allow the interpretation of the studied schist package as a representative of deep-marine sediments and tectonic slices of mantle ultramafics. Probably representing remnants of an accretionary wedge, this rock assemblage became incorporated in the Araçuaí orogen and was affected by the syn-collisional Barrovian metamorphic front between 575 and 540 Ma.